Transforming Antenatal Education in the Digital Era: The Impact of a Hybrid Intervention in Pregnant Women’s Behavior - Sri Widatiningsih; Mundarti; Christin Hiyana TD; Esti Handayani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Antenatal education is essential to reducing maternal mortality. However, limited access and time constraints reduce participation in conventional pregnancy classes. This study aims to evaluate the effectiveness of a hybrid antenatal education model in improving pregnant women's knowledge, attitudes, and practices (KAP) regarding maternal care. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted among 60 pregnant women in Magelang, Indonesia, from April to July 2024. Participants were randomly assigned to either a hybrid intervention group or a conventional care group. Data were collected at three time points and analyzed using Paired T-Tests, Independent T-Tests, and GLM-Repeated Measures. Results: The intervention group showed significant improvements in knowledge, attitudes, and practices (p< .005). The effect size was strongest for knowledge (Partial Eta Squared ?²=0.783). Age was identified as a confounding factor affecting practice (p=0.008). Conclusion: The hybrid antenatal education model significantly enhances maternal health behaviors, particularly knowledge, and provides a sustainable educational strategy. It is recommended for broader implementation in urban healthcare settings to improve antenatal care engagement and outcomes.